Two Birds, One Stone: The Effectiveness of Health and Environmental Messages to Reduce Meat Consumption and Encourage Pro-environmental Behavioral Spillover - Wolstenholme, Emily; Poortinga, Wouter; Whitmarsh, Lorraine (Frontiers in Psychology, 2020)
There is a growing consensus that reducing excess meat consumption will be necessary to meet climate change targets, whilst also benefitting people’s health. Strategies aimed at encouraging reduced meat consumption also have the potential to promote additional pro-environmental behaviours through behavioural spillover, which can be catalysed through an increased pro-environmental identity. Based on this, the current study tested the effectiveness of a randomised two-week messaging intervention on reducing red and processed meat consumption and encouraging pro-environmental behavioural spillover. Participants were UK undergraduate students (n = 320 at baseline) randomly allocated to four conditions in which they received information about the health, environmental, or combined (health and environmental) impacts of meat consumption, and a no-message control. The results showed that receiving information on the health and/or environmental impacts of meat was effective in reducing red and processed meat consumption compared to the control group during the intervention period, with some effects remaining one-month later. However, the intervention did not have any effect on pro-environmental identity and there was little evidence of behavioural spillover. Implications for future research and interventions aimed at reducing meat consumption are discussed.